Cytomegalovirus infection of the major duodenal papilla in a renal allograft recipient with severe biliary obstruction and acalculous cholecystitis. Issue 4 (23rd June 2013) - Riediger, C.; Beimler, J.; Weitz, J.; Zeier, M.; Sauer, P.
Abstract Cytomegalovirus (CMV) can cause severe infections with serious consequences in renal transplant recipients. Disseminated CMV infections can affect almost every organ, but obstructive cholestasis and cholangitis, as a consequence of a CMV‐induced papillitis, is extremely rare. We are reporting a rare case of obstructive cholestasis and cholecystitis due to CMV‐related inflammation of the major duodenal papilla in a 60‐year‐old woman 3 months after renal transplantation. In addition, the patient suffered from a disseminated CMV infection with ulcerative esophagitis and gastritis. Because of the severe CMV infection, failure of the renal graft occurred. Obstructive cholestasis was resolved through internal stenting, and the progressive cholecystitis necessitated an emergency cholecystectomy. Following antiviral therapy with ganciclovir, the gastrointestinal ulcerations regressed and renal function was restored. Diagnosis of the CMV‐related disease was established only in tissue samples, whereas standard serologic tests had failed.